2016
DOI: 10.31018/jans.v8i2.890
|View full text |Cite
|
Sign up to set email alerts
|

Attitude of rural youth towards agriculture as a means of livelihood

Abstract: The importance of agriculture to the socio-economic development of the country cannot be overemphasized. Agriculture sector is potentially the largest employment providing sector in the country. Despite this, unemployment is high among rural youth, who prefer to migrate to urban areas to take up low paying jobs. The present study was carried out mainly to find out the characteristics of rural youth and their attitude towards agriculture as a means of livelihood. The study was conducted in four villages in Udha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…The rural youth, irrespective of the educational level, must have realized the significance of agriculture as the major resource for their livelihood. The study was in agreement to the findings of Umunnakwe et al [6] and Gangwar and Kameswari [7].…”
Section: Education Vs Perceptionsupporting
confidence: 92%
“…The rural youth, irrespective of the educational level, must have realized the significance of agriculture as the major resource for their livelihood. The study was in agreement to the findings of Umunnakwe et al [6] and Gangwar and Kameswari [7].…”
Section: Education Vs Perceptionsupporting
confidence: 92%
“…This dilutes the value of the enterprise and drives the youths away from the industry. The result is in line with the finding of Gangwar and Kameswari (2016) that a positive attitude towards agricultural enterprises is key to participation. A respondent revealed that "youths do not participate in beekeeping because it is tiresome in sculpturing hives, and they prefer white-collar jobs.…”
Section: Attitudessupporting
confidence: 89%
“…This dependence is compounded by the fact that the availability of land suitable for agricultural is greatly limited. So, the population in hill region has yet to struggle hard for eking out their livelihoods largely from agriculture by putting larger numbers of their household members into the labour force (Mamgain, 2004). One of such hill state is Uttarakhand which is having this as one of the major problem of the state where the rate of migration from rural areas to the urban area is very high.…”
Section: Status Of Agriculture In Uttarakhandmentioning
confidence: 99%